2022
DOI: 10.1097/mcc.0000000000000947
|View full text |Cite
|
Sign up to set email alerts
|

Health inequities in out-of-hospital cardiac arrest

Abstract: Purpose of review Out-of-hospital cardiac arrest (OHCA) is a time-critical emergency in which a rapid response following the chain of survival is crucial to save life. Disparities in care can occur at each link in this pathway and hence produce health inequities. This review summarises the health inequities that exist for OHCA patients and suggests how they may be addressed. Recent findings There is international evidence that the incidence of OHCA is i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 86 publications
(118 reference statements)
0
11
0
Order By: Relevance
“…Whilst our study was limited with small numbers of individuals from ethnic minorities, the findings support other studies which have identified ethnic minorities encounter barriers accessing BCPR training, exacerbated by language difficulties. 38 Participation in our study was generally reflective of regional ethnicity, but focused studies within the region with ethnic minority study populations would help to better explain these differences.…”
Section: Discussionmentioning
confidence: 98%
“…Whilst our study was limited with small numbers of individuals from ethnic minorities, the findings support other studies which have identified ethnic minorities encounter barriers accessing BCPR training, exacerbated by language difficulties. 38 Participation in our study was generally reflective of regional ethnicity, but focused studies within the region with ethnic minority study populations would help to better explain these differences.…”
Section: Discussionmentioning
confidence: 98%
“… 4 , 5 , 6 , 7 , 8 There are several potential causes for this apparent disparity, including pre-existing chronic health inequalities, 24 OOHCA circumstances, access to public access defibrillation, 25 and also to specialist CAC care. 26 Limiting unwarranted variation in care based on ethnicity and SES is a priority of many healthcare systems across all conditions, including the NHS. 27 Indeed, in 2021, the NHS Race & Health Observatory advocated for people from minority ethnic backgrounds to be trained in CPR, 28 underlining the significant public health challenge and importance of investigating ethnic discrepancies in OOHCA care and outcomes.…”
Section: Discussionmentioning
confidence: 99%
“… 1 Survival after OHCA is poor, with a median survival to hospital discharge of 5.1% 2 . Patients who are underrepresented minorities, of lower socioeconomic status, and live in underserved communities have even lower rates of survival to discharge 3 . While survival after IHCA is generally considered better, studies have shown comparable survival among IHCA and OHCA patients when limited to patients who achieved return of spontaneous circulation (ROSC) and after adjusting for arrest characteristics (witnessed vs. unwitnessed, shockable vs. nonshockable presenting rhythm) 4 …”
Section: Out-of-hospital Cardiac Arrest (Ohca) Versus In-hospital Car...mentioning
confidence: 99%